1990
DOI: 10.1128/jcm.28.10.2285-2290.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two monkey species (Macaca mulatta and Macaca fascicularis) as possible models for human Helicobacter pylori disease

Abstract: Endoscopic, histologie, and microbiologie evaluations of 21 cynomolgus and 34 rhesus monkeys for naturally occurring Helicobacter pylori infection were done. H. pylori was never isolated from any cynomolgus monkey, but was found in 12 rhesus monkeys. A general correlation existed between a positive culture and a gastric inflammatory response. Inoculation challenges were then undertaken. Four cynomolgus and five rhesus monkeys received two different H. pylori strains isolated from humans. Five rhesus monkeys re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Experimental models of H pylori infection have been described using gnotobiotic piglets, 3 euthymic germ free mice, 4 athymic nude mice, 5 and monkeys. 6 The Mongolian gerbil also appears to be an appropriate animal model of H pylori infection. [7][8][9] Gastrointestinal diseases such as gastritis, gastric ulcer, and adenocarcinoma that mimic human H pylori infection can be studied in the Mongolian gerbil model.…”
mentioning
confidence: 99%
“…Experimental models of H pylori infection have been described using gnotobiotic piglets, 3 euthymic germ free mice, 4 athymic nude mice, 5 and monkeys. 6 The Mongolian gerbil also appears to be an appropriate animal model of H pylori infection. [7][8][9] Gastrointestinal diseases such as gastritis, gastric ulcer, and adenocarcinoma that mimic human H pylori infection can be studied in the Mongolian gerbil model.…”
mentioning
confidence: 99%
“…Several trials were done to establish animal models of H. pylon infection. The infection was successful in monkeys (9) and piglets (8, 22, 24) but unsuccessful in mice and rats (4, 6). These facts correlated well with our present data on H. pylon adhesion to the antral epithelial cells isolated from these anirpals.…”
Section: Discussionmentioning
confidence: 99%
“…Other attempts were made to clarify the pathogenesis by establishing animal models of H. pylon infection. These studies revealed that, while establishment of H. pylon infection was unsuccessful in germfree rodents such as mice and rats (4,6), the bacteria could colonize the stomachs of monkeys (9), gnotobiotic piglets (8,22,24), gnotobiotic dogs (31), nude mice (21), and Mongolian gerbils (37) when the animals were orally challenged. However, these studies did not reveal why the bacteria colonized the stomachs of some * Corresponding author.…”
mentioning
confidence: 99%
“…The primate model was described as a good model for human gastroduodenal diseases such as those induced by Helicobacter pylori (Euler et al 1990;Dubois et al 1996). Nevertheless, the ethical limitations linked to the use of primates, the cost to be supported and the difficulties to breed and to handle these species are limitations to carry out extensive investigations.…”
mentioning
confidence: 99%